تأثير تدخل دولة الامارات العربية المتحدة في الازمة الانسانية في النزاع المسلح غير الدولي في السودان خلال عامي 2023–2024 (The Impact of The United Arab Emirates' Intervention in the Humanitarian Crisis in the Non-International Armed Conflict in Sudan During 2023-2024) - Raihani Hafidzah Sinaga; Ida Susilowati (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
In 2023-2024, the conflict in Sudan heated up again due to tensions between the military and the Rapid Support Force paramilitary after the overthrow of President Omar Hassan Al-Bashir. This situation was exacerbated by the escalation of the conflict due to the intervention of the United Arab Emirates. This study aims to analyse the impact of the United Arab Emirates' intervention on the humanitarian crisis in Sudan. This study uses a qualitative research type with a descriptive analytical method and a humanitarian intervention approach from a realist perspective as the main approach. This study uses data analysis techniques, including data collection, reduction, processing, presentation, and conclusions. Data were taken from secondary sources such as academic journals, scientific articles, books, international documents, relevant news reports, and actors affected by the conflict. The results of this study indicate that the escalation of the conflict in Sudan due to the intervention of the United Arab Emirates has an impact on the Humanitarian Crisis. Several aspects show the effects of the United Arab Emirates intervention: first, the individual crisis as seen from the large number of fatalities due to the conflict and the group crisis in the form of ethnic massacres, structural marginalisation and systematic violence against a community. Second, the economic crisis is seen in the weakening of the currency, declining investment and decreasing availability of food supplies, which worsen the social conditions and lives of civilians in Sudan. Third, the food crisis is getting worse due to the hampered distribution of food, resources, and rising food prices. Fourth, the health crisis. This situation is worsened by the many injuries from war victims, lack of access to health services, and increasing diseases that spread amidst the chaos of the conflict. Fifth, the refugee crisis. The prolonged state of conflict in Sudan has forced thousands of Sudanese to flee both domestically and to neighbouring countries. Thus, the UAE's intervention in Sudan not only prolongs the conflict but also has an impact on the humanitarian crisis. This study provides insight into how intervention in a country in conflict can worsen the humanitarian crisis, leading to regional and global instability.Keywords: Intervention; Humanitarian Crisis; Conflict; Sudan; United Arab Emirates